Demographic profile and motivations of selected young entrepreneurs in Quezon City - Anonuevo, Khalehla M. (UP College of Home Economics, 2011)
The increasing number of young entrepreneurs going into business and their motivation, inspired the researcher to conduct this study to: identify which of the dimensions of motivation influences young entrepreneurs to engage in business; determine the correlation of their motivations to their demographic profile (Gender, Age, Civil Status, Educational Attainment, and Socio-economic Status); and identify learning experiences for inclusion in motivational programs for young entrepreneurs. The respondents were young entrepreneurs under 35 years old from Quezon City and were chosen through convenience sampling. The Pearson's r test was used to find the correlation between the respondents' demographic profile and the different motivators using the standard level of significance, 0.05. Results show that all the motivation dimensions (Accommodation, Achievement, Communitarianism, Escape, Independence, Money, Opportunity and Recognition) influences young female entrepreneurs more than males; Achievement, Independence, Communitarianism, Recognition, and Communitarianism influence married young entrepreneurs more than their single counterpart; Independence influence more those with higher family income. Learning experiences to strengthen Communitarisnism were also identified for motivational programs for young